Analysis of The Effectiveness of The Utilization of Kusuka Card In Fisherman Empowerment (Case Study Of Untia Fisherman Village, Bringkanaya Subdistrict, Makassar City) - Himawan, Bismar; Arief, Andi Adri; Ethrawaty Fachry, Mardiana; Amri, Andi; Wahid, Abdul (Program Studi Sosial Ekonomi Perikanan, Fakultas Ilmu Kelautan dan Perikanan, Universitas Hasanuddin, 2021)
This study aims to determine how fishermen's perceptions of the use of kusuka cards in supporting business activities. as well as to find out how the effectiveness of the fisherman card utilization in the fishermen empowerment program in Untia Fisherman Village, Bringkanaya Subdistrict, Makassar City. This research was conducted in January 2021, on fishermen who have a card I like in Kampung Nelayan Untia, Makassar City. The sampling method is purposive sampling because with several considerations, namely, the coastal area where the people are mostly fishermen, there are fishermen who have a card I like, there are community assistants who can also act as key informants, related to the general condition of Untia fishermen. This type of research used in this research is descriptive. The population in this study were fishermen of the untia fishing village who had a kusuka card and the number of fishermen who had a kusuka card was 75 people. The sampling method used in this study is the saturated sample method. The saturated sample method is a sampling technique when all members of the population are used as samples. The data collection techniques were interview and observation. With data analysis using a Likert scale. The research results obtained are fishermen's perception of the kusuka card in untia fishing village, namely the existence of this kusuka card is very important and very helpful for fishermen starting from getting help to the ease of joining the ministry of marine and fisheries programs, so this kusuka card provides many benefits that have been felt. for fishermen. The effectiveness of the Kusuka card in the fishing village is quite effective because it can help fishermen's activities at sea and there is a Person In Charge as the person in charge of handling the I like card if there are obstacles faced by fishermen.